Do increasing legal age at marriage and increased use of contraception will matter to achieve demographic goal: Revisiting the role of proximate determinants in Bangladesh - Rabbi, Ahbab Mohammad Fazle (Bangladesh Journal of Scientific Research, 2016)
According to 2010 world population prospects (WPP), Bangladesh is passing second phase of fertility transition. The recent aggregate fertility level (TFR) of Bangladesh is 2.3 births per woman, which is very close to the replacement level. This transition raises questions about possible factor for fertility decline in Bangladesh as uses of family planning methods are almost stable since last decade. Using recent national level survey data and the Bongaarts framework of the proximate determinants of fertility, an attempt has been made in this study to identify the factors responsible for such notable decrease in fertility level of Bangladesh. The results demonstrate that contraception appears as the most prominent determinant in fertility reduction in Bangladesh; followed by lactational infecundability, marriage and induced abortion. High proportion of adolescent marriages in Bangladesh yields high value of the index of marriage which consequently influences fertility level and in particular, adolescent fertility. Simulation on proportion married at adolescent ages suggest policy implication for raising the current legal age at marriage will decrease the proportion married at adolescent ages which with the increased use of contraceptive prevalence rate would help to achieve demographic objective in Bangladesh. Bangladesh J. Sci. Res. 28(1): 27-34, June-2015